A Study of Some Well-Known Results on Fuzzy Metric Space - Shahi, Nirak Kumar; Rana, Keshar Singh; Devkota, Hemant (Academic Journal of Mathematics Education, 2024)
In this paper, the notation of fuzzy metric space is re-introduced with different properties and we prove some well-known results on fuzzy metric space based on George – Veeramani approach.